Factors Controlling Terminus Position of Hansbreen, a Tidewater Glacier in Svalbard. Issue 2 (24th February 2021) - Błaszczyk, Małgorzata; Jania, Jacek A.; Ciepły, Michał; Grabiec, Mariusz; Ignatiuk, Dariusz; Kolondra, Leszek; Kruss, Aleksandra; Luks, Bartłomiej; Moskalik, Mateusz; Pastusiak, Tadeusz; Strzelewicz, Agnieszka; Walczowski, Waldemar; et al.
Abstract: The mechanism of glacier recession and its climatic controls are complex processes that differ across the Arctic region. Here, we investigate factors influencing front variations of Hansbreen, a glacier terminated in Hornsund fjord (SW Svalbard). We apply remote sensing data to observe glacier front fluctuations between 1992 and 2015 and compare them to atmospheric and oceanographic data, sea water depth at the terminus and surface velocity. Rate of subglacial meltwater discharge approximated by the seasonal positive degree‐day index (PDD) together with sea thermal conditions appear to be the main factors responsible for the fluctuations of the front of Hansbreen, while water depth at the front plays a secondary role. Taking into account ocean and air thermal conditions, the studied period has been divided into warm, cold and moderate years. The glacier retreated considerably throughout a bedrock overdeepening in the very warm period 2012–2014. This recession coincided with a slower ice flow due to intense subglacial runoff and increased submarine melting. The long‐term retreat was interrupted by glacier advances in colder years, regardless of water depth at the front. The slower recession rate was the combined effect of decreased subglacial melting and increased glacier movement associated with lower subglacial runoff. Although the seasonal PDD is a good indicator of the front fluctuations, the duration of the retreat and advance periods are strongly correlated with the sea surface temperature. Expected climate warming and an increase of water temperature in the West Spitsbergen Current will stimulate further recession of Hansbreen in future. Key Points: Changes in terminus position are driven by submarine melting and by subglacial runoff, indirectly affecting glacier velocity Synergy of increased sea temperature and deep water amplify the effect of subglacial runoff in warm years and can trigger glacier retreat Duration of the retreat and advance periods is strongly related to sea temperature, regardless of air temperature